(untitled) (Homiletic, 2015)
Postcolonial studies has been introduced to biblical studies, theology, and more recently to preaching. This article portrays postcolonial preaching as a locally rooted and globally conscious performance that seeks to create a Third Space so that the faith community can imagine new ways of being in the world. Postcolonial preaching must be done in the context of decolonizing worship, taking consideration of the use of symbols, liturgical texts, hymnody, scripture, and time and space. The author discusses how the preacher can engage the performative in postcolonial biblical studies and deal with heteroglossia in intercultural congregations.